The Effects of Cognitive and Visual Functions of Korean Elderly Taxi Drivers on Safe Driving Behavior - Yang Y; Lee H (Dove Medical Press, 2021)
YeongAe Yang,1,2 HyeJin Lee3,4 1Department of Occupational Therapy, College of Biomedical Sciences and Engineering, Inje University, Gimhae, Republic of Korea; 2Institute of Aged Life Redesign, Inje University, Gimhae, Republic of Korea; 3Department of Occupational Therapy, Choonhae College of Health Sciences, Ulsan, Republic of Korea; 4Department of Rehabilitation Science, Graduate School of Inje University, Gimhae, Republic of KoreaCorrespondence: HyeJin LeeDepartment of Occupational Therapy, Choonhae College of Health Sciences, 9, Daehak-gil, Ungchon-myeon, Ulju-gun, Ulsan, 44965, Republic of KoreaTel +82-10-8784-6389Fax +82-52-270-0319Email dnjstnddl6389@hanmil.netPurpose: In this study, we investigated the effect of visual and cognitive functions of elderly taxi drivers on safe driving behavior. We aimed to identify factors that interfere with safe driving in an aging Korean society in elderly taxi drivers.Participants and Methods: A total of 203 elderly taxi drivers, aged > 65, working at 3 companies in a single city were assessed over 4 weeks from December 1 to December 30, 2017, using the Motor-Free Visual Perception Test, Korean Montreal Cognitive Assessment, and Korean Safe Driving Behavior Measure. To examine the effects of cognitive and visual functions on driving behavior, we performed a stepwise multiple linear regression analysis (p< 0.05).Results: All 4 subdomains of safe driving behaviors were significantly correlated with the cognitive subdomains of attention and abstraction and the visual perception subdomains of visual closure 1 and figure-ground.Conclusion: More systematic assessments of the relationship between driving behavior and cognitive and visual function in elderly individuals are needed.Keywords: elderly, safe driving behavior measure, taxi driving, driving, cognitive function